2015
DOI: 10.1021/acs.jproteome.5b00512
|View full text |Cite
|
Sign up to set email alerts
|

DDX3Y, a Male-Specific Region of Y Chromosome Gene, May Modulate Neuronal Differentiation

Abstract: Although it is apparent that chromosome complement mediates sexually dimorphic expression patterns of some proteins that lead to functional differences, there has been insufficient evidence following the manipulation of the male-specific region of the Y chromosome (MSY) gene expression during neural development. In this study, we profiled the expression of 23 MSY genes and 15 of their X-linked homologues during neural cell differentiation of NTERA-2 human embryonal carcinoma cell line (NT2) cells in three diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 69 publications
7
59
0
Order By: Relevance
“…Because Y chromosome data was now available, specific consideration was given to Y-linked differentially expressed genes. The only large (2.3-fold increase) expression change detected in a Y-linked gene was in Usp9y , which is expressed in the human brain and implicated in sex-related brain differences, neuronal differentiation, 6062 and autism, 63 however expression (sequence counts) was low in both sample pools.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Because Y chromosome data was now available, specific consideration was given to Y-linked differentially expressed genes. The only large (2.3-fold increase) expression change detected in a Y-linked gene was in Usp9y , which is expressed in the human brain and implicated in sex-related brain differences, neuronal differentiation, 6062 and autism, 63 however expression (sequence counts) was low in both sample pools.…”
Section: Resultsmentioning
confidence: 98%
“…The X chromosome homolog Usp9x , however, was highly expressed but not differentially expressed between the treatment and control pools. Usp9y (ubiquitin specific peptidase 9, Y-linked) is one of several Y-linked genes implicated in brain sexual dimorphism during human development 103105 and its expression is increased during neural differentiation, 106 making it an interesting candidate for further study in schizophrenia pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these escape genes retain Y homology, although Y copies have been pseudogenized or have acquired distinct functions or expression patterns (e.g. [57,58]). Acquisition of XCI has been proposed to be a response to Y-gene degradation, suggesting some escapees are at an intermediate stage in this process [59].…”
Section: (C) Sexual Dimorphismmentioning
confidence: 99%
“…These low-abundance proteins are likely to exhibit their transcriptional expression at both tissue and subcellular specific manner (PE2 proteins) and may be involved in gene regulation in poorly understood regions of the genome [53]. Because of the large dynamic range of proteins in biological samples, low-abundance isoforms and proteoforms that may be associated with disease, can be extremely difficult to measure [54]. Proteomic analysis has shown that post-translational modifications can be different in alternative splicing variants and that amino-acid polymorphisms can generate additional variants.…”
Section: Challenges For the C-hppmentioning
confidence: 99%
“…The potential solutions for such problems may be: (i) the development of advanced software for spectral search methods, which can result in greater sensitivity and more accuracy in the search for the MPs [54, 55, 62], (ii) a combined solubilization method for the initial sample treatment step [63]; among the reagents, sodium deoxycholate and RapiGest showed good solubility and enzyme compatibility as well as easy removal in later steps prior to the MS analysis; (iii) the use of high-resolution mass spectrometry; and (iv) the use of RNA Seq analysis to better guide tissue selection and timing and to identify tissues or cells not commonly used for MS analyses [6466] ( Table 1 ). In particular for PE2 proteins, C-HPP investigators can approach to perform target proteomics in order to identify PE2 class MPs by utilizing genomics dataset (e.g., RNA-seq) obtained from some specific tissues or cell lines [30].…”
Section: Challenges For the C-hppmentioning
confidence: 99%